Sustained Swimming Training Is Associated With Reversible Filet Texture Changes of European Sea Bass (Dicentrarchus labrax L.) - Shi, C.; Wang, J.; Yang, Z.; Gao, X.; Liu, Y.; Wang, C. (Frontiers in Physiology, 2019)
This present study aimed to investigate the effect of training and detraining on the growth, chemical composition, white muscle fibers, and filet texture of the European sea bass (Dicentrarchus labrax L.). Fish were divided into control and training groups, which were subjected to water velocities of 0.2 and 1.0 body length per second (bl s−1), respectively, for 32 days (phase I). Half of the fish in the training group were then randomly selected and detrained at a velocity of 0.2 bl s−1 for another 32 days (detraining group), while the velocity of the remaining fish in the training group (1 bl s−1), and control group (0.2 bl s−1) remained unchanged (phase II). The results showed that the growth, body composition, and white muscle fiber densities of the control and trained fish were not significantly different in either phase. Training significantly altered the muscle fiber distribution (P < 0.05), with the training group having fewer 80–90 μm fibers than the control and detraining group at the end of the experiment (P < 0.05). The training group also had significantly higher values for white fiber muscle textural parameters (hardness, adhesiveness, cohesiveness, springiness, gumminess, and chewiness) in phase I (P < 0.05), and these parameters correlated significantly with pH (P < 0.05). However, these differences in texture and the pH correlation weakened when the fish were detrained in phase II. These results indicated that an increase in muscle pH after training may alter the flesh texture characteristics of sea bass. In addition, sustained swimming could induce a reversible change in the filet texture of sea bass.